(untitled) (Research, Society and Development, 2022)
The COVID-19 pandemic, which began at the end of 2019 in China, directly affected the mental health, not only of those who suffered from the disease, but also everyone who was involved in some way in the care of these patients. This study aims to analyze the prevalence of depression and anxiety during the pandemic period in which we live, through the methodology of a qualitative and quantitative literature review, in order to verify whether or not there was an increase in the number of people with symptoms. of depression and anxiety. It was noticed, through the research, that most of the studies identified that during the pandemic a greater number of people acquired such diseases that they did not have, also showing that women and younger people were the group of people who suffered the most from the disease. This is mainly due to the fact of having had direct contact with the Sars-CoV-2 virus, and also the change in the lifestyle of each one. The analyzed works also indicated that, in addition to the patients, a part of the health professionals also contracted signs of depression and anxiety, since they had to deal with an exhausting workday, or even witness situations never seen before.